Pengaruh Brand Image Dan Harga Terhadap Keputusan Pembelian Konsumen Pada PT. Tri Sapta Jaya Sibolga - Kandida Pespian Laia; Nelly Sinaga; Rahmadiah Hanum (EBISMA : Jurnal Ekonomi, Bisnis, Manajemen dan Akuntansi, 2026)
This study aims to analyze the effect of Brand Image and Price on Consumer Purchase Decisions at PT. Tri Sapta Jaya Sibolga. The research method used is a quantitative approach with data collected through questionnaires distributed to 40 respondents. Data analysis was conducted using validity and reliability tests, classical assumption tests, multiple linear regression analysis, correlation coefficient, determination coefficient, and hypothesis testing (t-test and F-test) using SPSS software. The results show that all research instruments are valid and reliable, and the data are normally distributed without multicollinearity and heteroscedasticity issues. Partially, Brand Image has a positive and significant effect on Purchase Decisions with a t-value of 3.161 and a significance level of 0.003, while Price also has a positive and significant effect with a t-value of 2.972 and a significance level of 0.005. Simultaneously, Brand Image and Price significantly affect Purchase Decisions with an F-value of 26.159 and a significance level of 0.000. The coefficient of determination of 0.586 indicates that 58.6% of the variation in Purchase Decisions can be explained by Brand Image and Price, while the remaining is influenced by other variables not examined in this study.